2018
DOI: 10.1108/jgm-06-2017-0022
|View full text |Cite
|
Sign up to set email alerts
|

Institutional discrimination of women and workplace harassment of female expatriates

Abstract: Purpose The purpose of this paper is to investigate workplace gender harassment of female expatriates across 25 host countries and consider the role of institutional-level gender discrimination as a boundary condition. Further, the study investigates the effects of workplace gender harassment on frustration and job satisfaction and general job stress as a moderator. Design/methodology/approach The sample is comprised of 160 expatriates residing in 25 host countries. The authors test the model using partial l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 83 publications
1
75
0
12
Order By: Relevance
“…With regard to discrimination, some expatriate destinations may generally be averse to the presence of foreigners thereby potentially strengthening the likelihood of crisis situations (cf. Bader, Stoermer, Bader, & Schuster, 2018). Forstenlechner (2010), for example, has shown how discrimination at the host country level may lead the expatriate to be, in their own opinion, more easily the prosecuted or targeted party, for example, in road accidents.…”
Section: The Host Country Domainmentioning
confidence: 99%
“…With regard to discrimination, some expatriate destinations may generally be averse to the presence of foreigners thereby potentially strengthening the likelihood of crisis situations (cf. Bader, Stoermer, Bader, & Schuster, 2018). Forstenlechner (2010), for example, has shown how discrimination at the host country level may lead the expatriate to be, in their own opinion, more easily the prosecuted or targeted party, for example, in road accidents.…”
Section: The Host Country Domainmentioning
confidence: 99%
“…Prior scholarship shows that institutional barriers and discrimination against women expatriates remain widespread (Bader, Stoermer, Bader, & Schuster, 2018), negatively impacting the selection and retention of women expatriates. First, the selection systems for expatriates are often informal and subjective (Linehan & Scullion, 2001), leading staffing decisions to be particularly susceptible to biases (Harris, 2002).…”
Section: The Unique Experiences Of Women Expatriatesmentioning
confidence: 99%
“…differential treatment) can impact women expatriate retention. This can take many forms, including harassment (Bader et al, 2018) and social isolation (Hutchings et al, 2012). In sum, decades of research have shown that women are likely to face more cultural constraints, corporate resistance, and stereotypes about their expatriation interest than their male peers (Adler, 1987;Altman & Shortland, 2008;Shortland, 2018b).…”
Section: The Unique Experiences Of Women Expatriatesmentioning
confidence: 99%
“…For instance, early scholars assessed the challenges and difficulties that come along with adjusting to a new environment (Black, 1988;Black & Gregersen, 1991;Black, Mendenhall, & Oddou, 1991) with the majority of subsequent research on adjustment applying a stress perspective (Takeuchi, 2010). Other scholars have gazed into darkness by looking at the risks of expatriation in hostile environments (Bader, Reade, & Froese, 2016;Bader & Berg, 2014;Bader & Manke, 2018;Bader & Schuster, 2015;McPhail & McNulty, 2015), discrimination and hostility (Bader, Stoermer, Bader, & Schuster, 2018;Hutchings, Michailova, & Harrison, 2013), and expatriate divorce (McNulty, 2015). Yet another stream of research has explored drivers of assignments failure.…”
Section: Introductionmentioning
confidence: 99%